Radiation characteristics of thin-wire V-antennas excited by arbitrary time-dependent currents. - Martin, R.G.
This paper studies, from the point of view of the traveling-wave approach, the transient radiation by V-antennas including the dependence of the maximum directivity on the interior angle, on the length of the arms and on the characteristics of the exciting pulse. As particular examples, the cases when the antenna is excited by a harmonic signal and a Gaussian pulse are analyzed and the results obtained using the traveling-wave approach are compared with the ones obtained using numerical methods
Keywords: Gaussian pulse; Arms length; Exciting pulse characteristics; Harmonic signal; Harmonic signals; Interior angle; Maximum directivity; Numerical methods; Radiation characteristics; Thin-wire V-antennas.; Time-dependent currents; Transient radiation; Traveling-wave V-antennas.; Traveling-wave approach